How do banking groups react to macroprudential policies? Cross-border spillover effects of higher capital buffers on lending, risk-taking and internal markets - Giuseppe Cappelletti; Aurea Ponte Marques; Carmelo Salleo; Diego Vila Martín (European Central Bank (ECB), 2020)
We study the impact of macroprudential capital buffers on banking groups' lending and risk-taking decisions, also investigating implications for internal capital markets. For identification, we exploit heterogeneity in buffers applied to other systemically important institutions, using information from three unique confidential datasets, including information on the EBA scoring process. This policy design induces a randomized experiment in the neighborhood of the threshold, which we use to identify the effect of higher capital requirements by comparing the change in the outcome for banks just above and below the cut-off, before and after the introduction of the buffer. The analysis is implemented relying on a fuzzy regression discontinuity and on a difference-in-differences matching design. We find that, when parent banks are constrained with higher buffers, subsidiaries deleverage lending and risk-taking towards non-financial corporations and marginally expanded lending towards households, with negative effects on profitability. Also, we find that parents cut down on holdings of debt and equity issued by their subsidiaries. Our findings support the hypothesis that higher capital buffers have a positive disciplinary effect by reducing banks' risk-taking while having a (temporary) adverse impact on the real economy through a decrease in affiliated banks' lending activity. Therefore, to ensure the effectiveness of macroprudential policy, it is essential that policymakers assess their potential cross-border effects.
Keywords: E44; E51; E58; G21; G28; 330; Macroprudential policy; Capital buffers; Lending; Risk-taking; Internal capital markets